2011
DOI: 10.5301/ijao.2011.6508
|View full text |Cite
|
Sign up to set email alerts
|

Method for Autologous Single Skin Cell Isolation for Regenerative Cell Spray Transplantation with Non-Cultured Cells

Abstract: Eight patients were treated (mean age 30.3 years, mean burn total body surface area 14%, mean Abbreviated Burn Severity Index (5 points). The mean time to complete re-epithelialization was 12.6 days. All patients exhibited wound healing with improved esthetic and functional quality. Our initial experience for the use of non-cultured cells using a two-enzyme approach with cell washing suggests shortened time for wound closure, suggesting that the method may potentially avoid longer-term complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 19 publications
0
29
0
Order By: Relevance
“…The provided wound irrigation can support either the cells present in the wound or the additionally sprayed autologous cells following a cell spray transplantation (19)(20)(21) (Fig. 1).…”
Section: Thoughts and Progressmentioning
confidence: 99%
See 1 more Smart Citation
“…The provided wound irrigation can support either the cells present in the wound or the additionally sprayed autologous cells following a cell spray transplantation (19)(20)(21) (Fig. 1).…”
Section: Thoughts and Progressmentioning
confidence: 99%
“…The cells are taken from a healthy area of the patient's own skin and expanded in culture dishes into cell sheets, which are then transferred to the patient as confluent and stratified multilayer sheets to cover large-area burns when donor sites are limited. Wood et al therefore introduced single-cell spray grafting of noncultured cells, which we implemented into our clinical practice (19,20). Disadvantages of these cultured keratinocyte sheets include long in vitro expansion times of 2-4 weeks to obtain the required cell number, while the differentiation of basal keratinocyte skin progenitor cells takes place in the in vitro situation (15)(16)(17)(18).…”
mentioning
confidence: 99%
“…Indeed, reconstitution or repair of dysfunctional cells through the addition of autologous cells has demonstrated early promise in improving wound closure after burn injury. [25][26][27][28] Several other variables may also affect the kinetics of wound closure in this model, including the mechanism of burn and the timing of eschar removal. Regarding the mechanism of burn, we found that burns resulting from either scald or contact demonstrated no significant differences in wound closure characteristics, which supports the notion that either method transfers heat in a similarly efficient manner.…”
Section: Discussionmentioning
confidence: 99%
“…17.10) [93][94][95][96], laser printing [97], or cell-spraying [98,99] devices for depositing hydrogel [100] that includes cells and possibly growth factors [101]. Most narrowly defined, "cell printing" most commonly utilizes inkjet-style printing (Fig.…”
Section: Hydrogel-based Cell Printing and Spraying For Bone Scaffoldsmentioning
confidence: 99%